Coxsackievirus B4 sewage-isolate induces pancreatitis after oral infection of mice - Benkoova, Brigita; Pospisilova, Michaela; Kramna, Lenka; Kissova, Renata; Berakova, Katarina; Klement, Cyril; Cinek, Ondrej; Bopegamage, Shubhada (FEMS microbiology letters, 2021)
Numerous serotypes which belong to the genus Enterovirus (EV) show variability in their virulence and clinical manifestations. They are also known to undergo changes caused by mutations and recombination during their circulation in the environment and the population. Various EV serotypes are prevalent in groundwater, wastewater and surface waters. Our previous studies showed that oral infection induces pancreatitis depending on specific conditions, such as gravidity, in an outbred murine model. Our aim in the present study was to further explore the pancreatic histopathology in an outbred mouse model following oral infection with clinical isolates from a patient who had aseptic meningitis and an isolate from a treated-sewage sample recovered from the residential area of the patient. The isolates were identified as coxsackievirus B4 (CVB4) in tissue culture. The CVB4 sewage-isolate induced pancreatitis after oral infection. In contrast, pancreatitis was absent following infection with the clinical isolates. Comparison of polyprotein sequences showed that the treated-sewage strains differed from the patient's isolates by 9 and 11 amino acids. We conclude that the isolates of clinical and environmental origin differed in their pathogenic properties and showed genetic variation.
Keywords: Coxsackievirus Infections; Pancreatitis; virulence; genetic variability; enterovirus B lidský; coxsackie virózy; pankreatitida; Virulence; Enterovirus B, Human; pancreatitis; Animals; lidé; Humans; zvířata; isolates; myši; odpadní vody; coxsackievirus B4; pathogenesis; Mice; Sewage